Expanding DEMON Sidestream Deammonification Technology Towards Mainstream Application. (1st December 2015) - Wett, B.; Podmirseg, S.M.; Gómez‐Brandón, M; Hell, M.; Nyhuis, G.; Bott, C.; Murthy, S.
ABSTRACT: : A cross‐Atlantic R&D‐cooperation involving three large utilities investigated the feasibility of mainstream deammonification—the application of partial nitritation/anammox for full‐plant treatment of municipal wastewater at ambient temperatures. Two major process components have been implemented, 1) bioaugmentation of aerobic‐ and anaerobic ammonia oxidizers (AOB and AMX) from the DEMON‐sidestream sludge liquor treatment to the mainstream and 2) implementation of hydrocyclones to select for anammox granules and retain them in the system. Different operation modes have been tested at laboratory‐ and pilot‐scale in order to promote the short‐cut (more direct anammox route) in nitrogen removal metabolism. At the full‐scale installation at Strass WWTP, stable repression of nitrite oxidizing biomass (NOB) has been achieved for several months. Significant anammox enrichment in the mainstream has been monitored while high efficiency in the sidestream‐process has been maintained (96% annual average ammonia removal).